2021
DOI: 10.3389/fonc.2021.685377
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Neoantigen-Targeted Induction of Pyroptosis and Ferroptosis: From Basic Research to Clinical Applications

Abstract: Neoantigens are tumor-specific antigens (TSAs) that are only expressed in tumor cells. They are ideal targets enabling T cells to recognize tumor cells and stimulate a potent antitumor immune response. Pyroptosis and ferroptosis are newly discovered types of programmed cell death (PCD) that are different from apoptosis, cell necrosis, and autophagy. Studies of ferroptosis and pyroptosis of cancer cells are increasing, and strategies to modify the tumor microenvironment (TME) through ferroptosis to inhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis (19,20). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis (19,20). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that activation of ferroptosis can overcome tumor development and reduce the sensitivity of the tumor to chemotherapy ( 8 ). Ferroptosis has been reported to modulate the TME to inhibit tumor progression and improve prognosis ( 19 , 20 ). Our study first developed a novel risk-scoring model based on 5 ferroptosis-related prognostic genes from SCLC data from the cBioPortal dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking CTLA-4 and PD-1 immunotherapies became a crucial part of cancer therapy [ 42 ]. For this purpose, PD-1 (CD279)/PD-L1 (CD274) and CTLA-4 expression were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Developing new approaches to boost anti-tumor immunity is critical because many tumors are non-responsive to immunotherapy due to a lack of tumor-infiltrating immune cells or tumor-released antigens. The emerging view suggests that pyroptosis releases inflammatory mediators and could alter TME through the influx of immune cells and eliciting tumor antigens [ 42 ]. This study indicated that the pyroptosis modification pattern was strongly correlated to TME, TMB, and the response to the anti-PD-1/L1 immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, three processes of cell death were characterized: apoptosis, necrosis, and autophagy. During the past decade or so, new types of cell death such as pyroptosis and ferroptosis have been identified and their importance gradually appreciated ( Yu et al, 2021 ). Indeed, there is growing evidence for a Ca 2+ related mechanism in ferroptosis in cancerous and noncancerous cells ( Chen P. et al, 2020 ; Angelova et al, 2020 ), suggesting a unique yet ubiquitous role of Ca 2+ in general cell death processes.…”
Section: Stim and Orai In Cell Survivalmentioning
confidence: 99%